2016
DOI: 10.1530/eje-15-1131
|View full text |Cite
|
Sign up to set email alerts
|

EJE PRIZE 2015: How does insulin resistance arise, and how does it cause disease? Human genetic lessons

Abstract: Insulin orchestrates physiological responses to ingested nutrients; however, although it elicits widely ramifying metabolic and trophic responses from diverse tissues, 'insulin resistance (IR)', a pandemic metabolic derangement commonly associated with obesity, is usually defined solely by blunting of insulin's hypoglycaemic effect. Recent study of monogenic forms of IR has established that biochemical subphenotypes of IR exist, clustering into those caused by primary disorders of adipose tissue and those caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 100 publications
4
28
0
7
Order By: Relevance
“…Notably, it should also be recognized that there has been uncertainty as to whether insulin resistance in PCOS has unique characteristics, since androgen excess per se may explain the development of insulin resistance in the insulin-sensitive tissues, such as fat, muscles and liver (46). In any case, the role of severe insulin resistance and very high circulating insulin in determining the PCOS phenotype in patients with SSIR states is confirmed on both clinical and basic research studies (69). One aspect of the association between PCOS and SSIR is that, in the last two decades, it has become increasingly clear that the responsible genetic factors of PCOS linked to SSIR are quite specific, and completely different with respect to the susceptible genes of the common PCOS, as proposed by recent genome-wide association and linkage studies (22,23).…”
Section: Severe Insulin-resistant Syndrome and Pcosmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, it should also be recognized that there has been uncertainty as to whether insulin resistance in PCOS has unique characteristics, since androgen excess per se may explain the development of insulin resistance in the insulin-sensitive tissues, such as fat, muscles and liver (46). In any case, the role of severe insulin resistance and very high circulating insulin in determining the PCOS phenotype in patients with SSIR states is confirmed on both clinical and basic research studies (69). One aspect of the association between PCOS and SSIR is that, in the last two decades, it has become increasingly clear that the responsible genetic factors of PCOS linked to SSIR are quite specific, and completely different with respect to the susceptible genes of the common PCOS, as proposed by recent genome-wide association and linkage studies (22,23).…”
Section: Severe Insulin-resistant Syndrome and Pcosmentioning
confidence: 99%
“…A physical sign always present in SSIR is acanthosis nigricans. Other physical signs of SSIR, although not always present, are unusual severe combined dyslipidemia (high triglycerides and low high-density lipoprotein-cholesterol levels) sometimes complicated by unusually severe hepatic steatosis and early-onset hypertension (65,69). The prevalence of PCOS secondary to SSIR has not been formally assessed, though referrals to our center in the last 10 years suggest a rate of approximately 1.5% among patients visiting the out-patient clinic for symptoms of PCOS (oligo-amenorrhea, hirsutism, infertility).…”
Section: Severe Insulin-resistant Syndrome and Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the patient described by Chen et al [15] showed quite low IGF-1 levels and an atrophic pituitary on MRI. Numerous genomic syndromes associated with short stature are caused by genetic defects in fundamental cellular processes [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Many diseases are accompanied with imapired glycemic control and insulin resistance. 9 Phosphorylation of Insulin Receptor Substrates (IRS) is crucial for insulin signalling cascade, which in turn activates the mitogen-activated protein kinase (MAP-Kinase) with major mitogenic effects and phosphatidylinositol-3-Kinase (PI-3K) with prominent metabolic properties including appropriate cellular glucose distribution. 10 Coenzyme Q10 might induce the tyrosine kinase and phosphatidylinositol 3 kinase (PI3k) activity in liver.…”
mentioning
confidence: 99%